Using of the biofeedback in rehabilitation of patients with mercury intoxication - M. P. Diyakovich; P. V. Kazakova; Ye. V. Katamanova; D. V. Rusanova (Бюллетень сибирской медицины)
The study results of using the biological reverse connection training with the musical therapy in the rehabilitation of the patients with the chronic mercury intoxication are represented in this paper. The positive effect of the BRC-training on processes concentration of retention, some subscales of the life quality, the functional state of the central afferent conducting structures as well as the neurophysiologic balance of the bioelectrical brain activity have been indicated.